Experimental Investigation of Single and Intermittent Light Non-Aqueous Phase Liquid Spills Under Dynamic Groundwater - Almaliki, Doaa F.; Ramli, Harris; Zaiter, Ali (Civil Engineering Journal, 2025)
The groundwater contamination from petroleum by-products represented in Light Non-Aqueous Liquid (LNAPL) under groundwater table fluctuations has become a serious environmental problem. For this reason, developing a rapid response strategy incorporating experimental characterization of LNAPL distribution trajectories is crucial for assessing the threats of LNAPL contaminants in the subsurface environment. In this study, the influence of various LNAPL spills in a porous medium under dynamic groundwater conditions was investigated using the Simplified Image Analysis Method (SIAM). Single and intermittent LNAPL (diesel) spills of total volume (400 and 800 ml) were examined in a river sand ‎two-dimensional tank (70 cm × 70 cm × 3.5 cm) under the effect of groundwater table fluctuation. The results indicated that the contaminant was distributed above h=28 cm in the 400 ml LNAPL spill. However, it migrated below h=28 cm, and its saturation reached 36% when the LNAPL volume raised to 800 ml. The LNAPL saturation in the case of four LNAPL intermittent spills was more evenly distributed through the tank depth than in the cases of a single spill of 800 ml and two intermittent spills of 400 ml. Furthermore, LNAPL migrated to a larger depth in the system (h=18.5 cm) only in the case of four LNAPL intermittent spills and under groundwater table fluctuation, which poses a significant threat to the groundwater. This study highlights the importance of the effect of various LNAPL spills under dynamic groundwater conditions, which can offer valuable guidance for developing remediation schemes. Doi: 10.28991/CEJ-2025-011-01-017 Full Text: PDF